Intensive Care Nurse Workload and Patient Acuity in Sfax, Tunisia: A COVID-19 Global Process Improvement Project. - Jlassi, Jihene; Lehyani, Fatma; Zouari, Alaeddine (Nursing Economic$)
This project aimed to improve nurses' satisfaction by implementing a mathematical model to ensure the balancing of nursing workload and equity. An integer program was used to assign nurses to patients in several scenarios to minimize excess workload. An applied mathematical model was validated to an intensive care unit of a COVID-19 center in Sfax, Tunisia. Computational and numerical results suggest nurse-patient assignment models can achieve a balanced work assignment.